Ammianus after Julian : the reign of Valentinian and Valens in Books 26-31 of the Res Gestae - Boeft, J. den; Drijvers, Jan Willem; Hengst, Daniël den; Teitler, H. C. (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2007)
The papers in this volume treat historical, historiographical and literary aspects of the last six books of Ammianus Marcellinus' Res Gestae, which deal with the period between the death of Julian (363) and the Roman defeat at Hadrianople (378).